ANALISIS PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR INTERNAL - Trie Sartika Pratiwi; Padriyansyah .; Dewi Kharisma Putri (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
The purpose of this research is to identify organizational commitment, organizational culture and leadership style which affect internal auditor’s performance. This research uses 35 internal auditors of PT. Telekomunikasi Indonesia Tbk, as respondents. Purposive sampling and multiple regression model are used in the research. The result show that organizational commitment and leadership style didn’t have significant effect on internal auditor’s performance, while organizational culture have significant effect on internal auditor’s performancce and significant. All variables are simultaneously affected to internal auditor’s performance.Keywords: organizational commitment, organizational culture, leadership style, internal auditor’s performance.